Toward an Integrated Policy Framework. (Policy Papers; Policy Paper ;, 2020)
Policymakers often face difficult tradeoffs in pursuing domestic and external stabilization objectives. The paper reflects staff's work to advance the understanding of the policy options and tradeoffs available to policymakers in a systematic and analytical way. The paper recognizes that the optimal path of the IPF tools depends on structural characteristics and fiscal policies. The operational implications of IPF findings require careful consideration. Developing safeguards to minimize the risk of inappropriate use of IPF policies will be essential. Staff remains guided by the Fund's Institutional View (IV) on the Liberalization and Management of Capital Flows.